THE IMPLEMENTATION OF BANDUNG MASAGI PROGRAM TOWARDS STUDENTSâ€™ CHARACTER BUILDING IN SOCIAL SCIENCE INSTRUCTION - Sutriani, Ayu (International Journal Pedagogy of Social Studies, 2019)
This study is motivated by the urgency of early character building through value investment of Sundanese local wisdom â€œBandung Masagiâ€. This study focuses on the efforts concerning studentsâ€™ character building through the implementation of Bandung Masagi program, the values application of Bandung Masagi program towards the studentsâ€™ character building in Social Science learning, and the impacts of the implementation of Bandung Masagi programâ€™s values application towards the studentsâ€™ character building in Social Science learning. This study used descriptive method with qualitative approach. The data of this study were collected in SMP Kartika XIX-2 Bandung by three techniques which are interviews, observation, and documentation study. This study shows that Bandung Masagi program is a good effort to build the nationsâ€™ character based on Sundaneseâ€™s local wisdom value by challenging the students to participate openly in every character building activities. The implementation of the values application of Bandung Masagi program in the research site went well since the school conducts the values application of Bandung Masagi in both extracurricular activities and in-class learning. Therefore, the students can optimize their self-potentialities to build a noble character like the Sundaneses, covering the values of religiosity, Sundaneseâ€™s culture, environmental caring, and state defense.